PENGGUNAAN SMART CONTRACT PADA TEKNOLOGI BLOCKCHAIN UNTUK TRANSAKSI JUAL BELI BENDA TIDAK BERGERAK - Fikri, Effrida Ayni; Anggoro, Teddy (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
The advancement of technology has impact on the notarization process. Before blockchain technology being introduced, the notarization process had been done in traditional matters: seller meets buyer, negotiation process, contract making, the parties should be known by the notary, the parties signed the contract, and so on. Those stuff are not relevant anymore with smart contract, because the basic idea of the smart contract’s existence is eliminating the function of the intermediary, so the parties could be connected directly and virtually, without the intervention from the middleman. All the ease of transaction provided by the smart contract does not necessarily eliminte it from shortcomings. The burden of proof on smart contracts is still questionable because, physically, smart contracts can only be accessed by all the parties involved.